Analisis peran senam otak terhadap fungsi kognitif lansia: A literature review - Juwari, Juwari; Ardian, Iwan; Luthfa, Iskim; Setyowati, Wahyu Endang (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The elderly are an age group vulnerable to cognitive decline due to degenerative processes. Impaired cognitive function can impact quality of life, independence, and the risk of dementia. One non-pharmacological intervention considered effective in maintaining and improving cognitive function in the elderly is brain gym, which combines simple physical movements with mental stimulation. Purpose: To analyze the role of brain gym on cognitive function in the elderly. Method: Literature review research of scientific articles through research journal databases and internet searches related to the role of brain gymnastics on cognitive function in the elderly for the period 2018 to 2025. The literature review process begins with topic selection, followed by a study search through Google Scholar, PubMed, Scopus, and EBSCO sites, with the search keywords